X-linked hypophosphatemic rickets--a report of 2 cases and review of literature - Yong, S.M.; Saw, Aik (Malaysian Medical Association, 2000)
We report two cases of x-linked dominant hypophosphatemic rickets involving a man and his daughter. The family tree consists of 44 members with 13 of them having short stature and bowing of the lower limbs. The study of this family tree strongly suggests an x-linked dominant inheritance.